Differentiation of pluripotent stem cells into striatal projection neurons: a pure MSN fate may not be sufficient - Reddington, Amy E.; Rosser, Anne E.; Dunnett, Stephen B. (Frontiers in Cellular Neuroscience, 2014)
Huntington’s disease (HD) is an autosomal dominant inherited disorder leading to the loss of DARPP-32 medium spiny projection neurons (‘MSNs’) in the striatum. The relative specificity of cell loss early in HD has made cell replacement by neural transplantation an attractive therapeutic possibility. Transplantation of human fetal striatal precursors has shown ‘proof-of-principle’ in clinical trials; however, the practical and ethical difficulty associated with sourcing fetal tissue has stimulated the need to identify alternative sources of donor cells that are more readily available and suitable for standardisation. The first generation of protocols to generate DARPP-32 positive MSN-like neurons from pluripotent stem cells are now available and have been successfully grafted in animal models of HD. However, whether these grafts can provide stable functional recovery to the level that can regularly be achieved with primary fetal striatal grafts remains to be demonstrated. Of particular concern, primary fetal striatal grafts are not homogeneous; they contain not only the MSN subpopulation of striatal projection neurons but also include diverse neuronal and glia cell types of the mature striatum that certainly contribute to normal striatal function. By contrast, present protocols for pluripotent stem cell differentiation just target specifying neurons of an MSN lineage, and evidence for functional integration of stem-cell derived grafts is correspondingly limited. Indeed, consideration of the features of full striatal reconstruction that is achieved with primary fetal striatal grafts suggests that effective stem cell-based therapy in HD will require that graft protocols be developed to allow inclusion of multiple striatal cell types, including interneurons and striatal glia. A rational solution to this technical challenge requires that we re-address the underlying question – what constitutes a functional striatal graft?